The Role of Transformational Leadership in Enhancing Teacher and Student Motivation - Mohammad Syamsul Maarif; Rugaiyah Rugaiyah; Linda Ika Mayasari (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2026)
Abstract: This study aims to analyze the role of transformational leadership in enhancing teacher and student motivation in educational institutions. The study employs a literature review approach by examining 20 relevant scholarly journal articles published between 2016 and 2024. Transformational leadership is understood as a leadership style oriented toward positive change by emphasizing vision, inspiration, emotional support, and intellectual stimulation for its followers. In the context of education, transformational leaders, such as school principals or institutional heads, have the ability to create an inspiring educational vision, build strong interpersonal relationships with teachers and students, and encourage innovation in both teaching and school management. The analysis results indicate that transformational leadership has a significant impact on improving teacher motivation. Teachers become more enthusiastic in teaching, more open to change, and more committed to developing their professional skills. Furthermore, students also show increased learning motivation, active engagement in class, and greater self-confidence. Leadership that fosters a positive and supportive school climate strengthens interpersonal relationships within the educational environment, enhances collaboration among teachers, and builds a collaborative culture that supports the creation of innovative learning. Transformational leadership also plays an important role in the development of adaptive curricula, the creation of a conducive work environment, and the enhancement of teacher job satisfaction. Overall, the findings show that this leadership style can be an effective strategy in creating educational institutions that are not only productive but also adaptive to ongoing global challenges. Therefore, educational leaders are encouraged to adopt the principles of transformational leadership in order to strengthen the intrinsic motivation of both teachers and students in achieving optimal educational goals. Keywords: Transformational Leadership, Teacher Motivation, Student Motivation.